Genome sequence of Halovibrio sp. HP20-59 as a promising polyhydroxybutyrate producer - Adhvaryu, Shivani; Kiskova, Jana; Piknova, Maria; Farkasova, Veronika; Buchtikova, Iva; Kourilova, Xenie; Kizovsky, Martin; Benesova, Marketa; Samek, Ota; Obruca, Stanislav; Pristas, Peter (Applied microbiology and biotechnology, 2026)
Since plastics pose the greatest threat to humanity, it is essential to find an economic and sustainable solution to combat environmental pollution. In this study, the ability of polyhydroxyalkanoates (PHA) production by the halophilic bacterium Halovirbrio sp. HP20-59 in the presence of different carbon sources was examined. The strain showed a selective substrate preference, with the highest PHA production (reaching up to 73% of cell dry weight) in the presence of galactose, while fructose, arabinose, glycerol and xylose resulted in lower accumulation. Phylogenetic analysis based on the 16S rRNA gene sequence and whole-genome sequencing confirmed the HP20-59 strain as a novel species within the Oceanospirillales order. Draft genome showed a size of 4,165,370 bp with a GC content of 55.1% and a complete set of pha genes. The comparative analysis of the phaC gene identified a 638 amino acid-long class I poly(R)-hydroxyalkanoic acid synthase, showing 91% similarity to Halovibrio variabilis and 89% similarity to species within the Vreelandella genus, suggesting a possible horizontal gene transfer of the pha gene cluster. These findings highlight the unique genetic and metabolic characteristics of Halovibrio sp. HP20-59, making it a promising candidate for industrial PHA production and a valuable resource for research on sustainable biopolymers. KEY POINTS: The first study of PHB production by the halophilic Halovibrio spp. The highest level of PHB production observed using glucose, galactose, and sucrose. phaCAB operon possibly acquired by horizontal gene transfer from Vreelandella sp.
Keywords: uhlík; Genome, Bacterial; Polyhydroxyalkanoates; Halovibrio; zastoupení bazí; genom bakteriální; Oceanospirillales order; Base Composition; sekvenční analýza DNA; polyhydroxyalkanoáty; sekvenování celého genomu; fylogeneze; multigenová rodina; Oceanospirillaceae; Carbon; Halophiles; DNA, Bacterial; RNA ribozomální 16S; Whole Genome Sequencing; DNA bakterií; Multigene Family; Raman spectroscopy; acyltransferasy; Sequence Analysis, DNA; polyhydroxybutyráty; hydroxybutyráty; PHA synthase (PhaC); Acyltransferases; RNA, Ribosomal, 16S; Polyhydroxybutyrates; Phylogeny; Hydroxybutyrates